'MusiMath' and 'Academic Music' – Two music‐based intervention programs for fractions learning in fourth grade students. Issue 4 (23rd July 2019) - Azaryahu, Libby; Courey, Susan Joan; Elkoshi, Rivka; Adi‐Japha, Esther
Abstract: Music and mathematics require abstract thinking and using symbolic notations. Controversy exists regarding transfer from musical training to math achievements. The current study examined the effect of two integrated intervention programs representing holistic versus acoustic approaches, on fraction knowledge. Three classes of fourth graders attended 12 lessons on fractions: One class attended the 'MusiMath' holistic program ( n  = 30) focusing on rhythm within the melody. Another class attended the 'Academic Music' acoustic program (Courey et al., Educ Stud Math 81:251, 2012) ( n  = 25) which uses rhythm only. The third class received regular fraction lessons (comparison group, n  = 22). Students in both music programs learned to write musical notes and perform rhythmic patterns through clapping and drumming as part of their fraction lessons. They worked toward adding musical notes to produce a number (fraction), and created addition/subtraction problems with musical notes. The music programs used a 4/4 time signature with whole, half, quarter and eighth notes. In the math lessons, the students learned the analogy between musical durations and 1 2, 1 4, 1 8 fractions, but also practiced fractions other than 1 2, 1 4, 1 8 . Music and math were assessed before, immediately following, and 3‐ and 6‐months post‐intervention. Pre‐ to post‐intervention analyses indicated that only the 'MusiMath' group showed greater transfer to intervention‐trained and untrained fractions than the comparison group. The 'Academic Music' group showed a trend on trained fractions. Although both music groups outperformed the comparison group 3‐ and 6‐months post‐intervention on trained fractions, only the 'MusiMath' group demonstrated greater gains in untrained fractions. Gains were more evident in trained than in untrained fractions. A video abstract of this article can be viewed at https://youtu.be/uJ_KWWDO624 Abstract : The current study examined the effect of two integrated music‐math intervention programs ('MusiMath' acoustic vs. 'Academic Music' holistic approach) on fraction knowledge in fourth graders. The music programs explicitly made the analogy between whole, half, quarter and eighth notes and 1 2, 1 4, 1 8 fractions, and were tested 3‐ and 6‐months post‐intervention. An advantage in both intervention‐trained ( 1 2, 1 4, 1 8 ) and untrained (e.g., 1 3, 1 5, 1 6 ) fractions was found only for the holistic program vs. the comparison group.